Temporal variations in the diagnostic performance of chest CT for Covid-19 depending on disease prevalence: Experience from North-Eastern France. Issue 134 (January 2021) - Ohana, Mickaël; Muller, Joris; Severac, François; Bilbault, Pascal; Behr, Martin; Oberlin, Mathieu; Leyendecker, Pierre; Roy, Catherine
Highlights: Chest CT accuracy was 85.4 % during ascending, peak and descending phases of the first Covid-19 wave. It was not significantly different between chest (4 readers, accuracy 86.4 %) and general (6 readers, accuracy 85.1 %) radiologists, with a probability of equivalence ≥ 95 %. There were important variations of CT predictive values whereas CT specificity remained stable over time. Abstract: Rationale and Objective: The purpose of this work was to analyze temporal variations in the diagnostic performance of chest CT for Covid-19 throughout the first wave, depending on disease prevalence variations between the ascending, peak and descending phases of the epidemic in North-Eastern France. Materials and Methods: From March 6th to April 22nd 2020, all consecutive adult patients referred to the "Covid-19 clinic" of our Emergency Department with the availability of chest CT and of at least one RT-PCR result were retrospectively included in the present study. Chest CT was considered positive when typical Covid-19 lesions were observed (bilateral and predominantly peripheral and sub-pleural ground glass opacities and/or alveolar consolidations). RT-PCR results were considered as the reference standard. Ascending, peak and descending phases were determined based on the number of CT scans performed daily. CT diagnostic performance were calculated and variations between phases were tested for equivalence or difference using Bayesian methods. Results: 2194 consecutive chest CT were analyzed. Overall CT diagnostic performance was Se = 84.2 [82.0 ; 86.3], Sp = 86.6 [84.5 ; 88.5], PPV = 86.1 [84.0 ; 88.1], NPV = 84.7 [82.6 ; 86.7] and accuracy = 85.4 [83.9 ; 86.8], with no significant differences between chest and non-chest radiologists. Variations between the ascending (11 days, 281 chest CT, disease prevalence 37.0 %), the peak (18 days, 1167 chest CT, disease prevalence 64 %) and the descending phases (19 days, 746 chest CT, disease prevalence 32.2 %) were highest for PPV and NPV with a probability of difference >99.9 %, and smallest for accuracy and specificity with a probability of equivalence >98.8 %. Conclusion: In a homogenous cohort of 2194 consecutive chest CT performed over a 7-week epidemic wave, we observed significant variations of CT predictive values whereas CT specificity appeared marginally affected.